Contemporary life threat in pneumonology - Płusa, Tadeusz (Przewodnik Lekarza/Guide for GPs, 2010)
Among the causes responsible for the damage of the respiratory tract should be incorporated into viral and bacterial infections, possible effects of bioterrorism and physico-chemical factors at the time of multiorgan injuries. Each of these factors can lead to severe inflammatory response and shock. Management must take into account the rapid and accurate diagnostic tests, with simultaneous administration of antibiotics and immediate anti-shock treatment. Knowledge of contemporary recommendations developed by expert panels helps correct treatment and the ability to avoid serious complications.